RECONSTRUCTING THE PROPHETIC CONCEPT OF JUSTICE: An Isnād-cum-Matn Analysis of the Hadith - Syihabuddin, Wildan; Alim, Skrghnm; Qur'aniyah, R.A.S; Huda, Ahmad Alamul; Ashimulloh, Ahmad (RIWAYAH, 2026)
Justice (al-‘adl) constitutes one of the fundamental principles of Islamic teachings, as reflected in the traditions of the Prophet Muhammad. Among the traditions that embody this principle is the hadith, “unsur akhaka zaliman aw mazluman” (“help your brother, whether he is the oppressor or the oppressed”). Although Isnad-cum-Matn Analysis (ICMA) has become increasingly prominent in contemporary hadith studies, existing scholarship has predominantly focused on examining the authenticity of hadiths, while its application to reconstructing the concept of justice contained within prophetic traditions remains relatively limited. This study aims to analyse the concept of justice embodied in this hadith, examine the historical validity of its isnad and matn through Harald Motzki’s ICMA approach, and explore its relevance to contemporary social contexts. Employing a qualitative library research method, the study involves collecting all available variants of the hadith, mapping their transmission networks, assessing the reliability of the narrators, comparing textual variations, and integrating the results of both isnad and matn analyses. The findings demonstrate that the hadith possesses strong historical validity, as evidenced by the multiplicity of transmission lines and the consistency of its substantive meaning. The reconstruction of the hadith’s meaning reveals that justice encompasses corrective, preventive, and social dimensions through the protection of victims, the prevention of oppressive behaviour, and the rejection of group fanaticism (‘asabiyyah). This study contributes to the advancement of hadith studies on justice, strengthens the application of ICMA in hadith scholarship, and provides an ethical foundation for promoting social justice in contemporary society. Keadilan (al-‘adl) merupakan salah satu prinsip fundamental dalam ajaran Islam sebagaimana tercermin dalam hadis-hadis Nabi Muhammad saw. Salah satu hadis yang merepresentasikan prinsip tersebut adalah hadis “unsur akhaka zaliman aw mazluman” (tolonglah saudaramu, baik ketika ia berbuat zalim maupun ketika ia dizalimi). Meskipun pendekatan Isnad-cum-Matn Analysis (ICMA) semakin berkembang dalam studi hadis kontemporer, kajian yang ada umumnya masih berfokus pada pengujian autentisitas hadis, sedangkan penerapannya dalam merekonstruksi konsep keadilan yang terkandung dalam hadis masih relatif terbatas. Penelitian ini bertujuan untuk menganalisis konsep keadilan yang termuat dalam hadis tersebut, menguji validitas historis sanad dan matannya melalui pendekatan ICMA Harald Motzki, serta mengkaji relevansinya dalam konteks sosial kontemporer. Penelitian ini menggunakan metode kualitatif berbasis studi kepustakaan dengan menghimpun seluruh varian hadis, memetakan jaringan transmisi, menganalisis kualitas para perawi, membandingkan variasi matan, serta mengintegrasikan hasil analisis sanad dan matan. Hasil penelitian menunjukkan bahwa hadis tersebut memiliki validitas historis yang kuat, yang ditunjukkan oleh keragaman jalur periwayatan dan konsistensi substansi teksnya. Rekonstruksi makna hadis mengungkapkan bahwa keadilan dalam hadis tersebut mencakup dimensi korektif, preventif, dan sosial melalui perlindungan terhadap korban, pencegahan terhadap pelaku kezaliman, serta penolakan terhadap fanatisme kelompok (‘asabiyyah). Penelitian ini berkontribusi pada pengembangan kajian hadis tentang keadilan, memperkuat penerapan ICMA dalam studi hadis, serta menyediakan landasan etis bagi penguatan keadilan sosial dalam masyarakat kontemporer.